Elements of heat transfer - Jacob, Max (John Wiley& Sons, 1957)
Contents: Thermnal Conductivity, Conduction of heat in the steady state, Conduction of heat in the unsteady state, Steady-State heat conduction in bodies with heat sources, Introduction to the dimensional analysis of convection, ....